PENGARUH ESG DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Sektor Nonkeuangan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Arfina Devinta; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) Disclosure on firm value, the effect of ESG Disclosure on financial performance, the effect of financial performance on firm value, and the mediating role of financial performance in the relationship between ESG Disclosure and firm value. Firm value is proxied by Tobin's Q, financial performance is proxied by return on assets (ROA), and ESG Disclosure is measured using Bloomberg ESG Disclosure Score. This study uses secondary data from Bloomberg Terminal, annual reports, and financial statements of non-financial companies listed on the Indonesia Stock Exchange during the 2021-2024 period. The sample was selected using purposive sampling and consisted of 148 companies with 436 firm-year observations based on a time-lag scheme. Hypotheses were tested using multiple linear regression and PROCESS Macro Model 4 with 5,000 bootstrap samples through SPSS 27. The results show that ESG Disclosure has no significant direct effect on firm value. ESG Disclosure has a positive and significant effect on financial performance, and financial performance has a positive and significant effect on firm value. Furthermore, financial performance fully mediates the relationship between ESG Disclosure and firm value. These findings indicate that the benefits of ESG Disclosure are more visible when reflected in financial performance before being appreciated by the market.